Aging behavior of metal oxide aerogels - Suh, DJ; Park, TJ; Sonn, JH; Han, HY; Lim, JC (KOREAN INST CHEM ENGINEERS, 2000)
Aerogels of titania, zirconia, niobia, and silica were prepared by CO2 supercritical drying of the corresponding alcogels. Their porous texture could be modified by further aging of the alcogels. This kind of textural modification was found to be different according to the nature of the metal precursor and sol-gel conditions.
Keywords: SILICA